Electrochemical fabrication of an efficient cobalt–iron oxide/graphene heterostructure by a three-electrode system for electrocatalytic oxygen evolution reaction. (24th August 2022) - Xiao, He; Cheng, Xiaoru; Jing, Yanying; Zhao, Man; Zhang, Li; Wu, Haishun; Jia, Jianfeng
Abstract : Electrosynthesized cobalt–iron oxide/graphene heterostructure by a three-electrode electrolysis system for efficient oxygen evolution reaction. Abstract : To acquire low-cost efficient electrocatalysts for oxygen evolution reaction (OER), a cobalt–iron oxide/graphene hybrid (Co–Fe/G) is fabricated by a facile three-electrode synthesis method. In the course of electrosynthesis, the exfoliation of graphite into graphene is combined with the preparation of cobalt–iron oxide, which greatly simplifies the procedure. The obtained Co–Fe/G exhibits an overpotential of 297 mV at 10 mA cm −2, much lower than that of RuO2 (341 mV 10 mA cm −2 ) with a difference of 44 mV. The characterization results reveal that the superior OER performance of Co–Fe/G is attributed to the composition synergy between the Co and Fe components. The electron transfer over the Fe–O–Co interfacial species along the O bridge not only adjusts the intrinsic electron structure towards a favorable adsorption performance for improving the OER performance but also enhances the conductivity. Moreover, the combined contribution of Co and Fe components enhances the electrochemical active surface area, which in turn promotes the OER activity.